A Study of Cyber Safety Awareness among Students and Educational Initiatives - Panjani, Harshita; Mudgal, Alka (Indian Journal of Educational Technology, 2025)
In the digital era, cyber safety education in schools has become paramount in ensuring the ethical use of technology and responsible digital citizenship among students. Technological integration in education demands a safe online environment for students. Moreover, after the COVID-19 pandemic, an exponential increase in the use of the internet in India can be observed, as a hybrid model of teaching-learning has been implemented since then. With an increase in the usage of the internet and technological advancements in the field of education, the risk of cybercrime and online threats has also increased. Thus, cyber safety awareness is crucial as students are exposed to a variety of online risks. This research delves into various aspects of cyber safety education in schools, its significance in making students robust and responsible netizens, and the role of educators in fostering a safe online environment. A survey was conducted to assess cyber safety awareness among middle and secondary-level students of two age groups (12-15 years and 15-18 years). The result of the survey revealed that the majority of students were not well aware of safe internet use and digital practices. Cyber safety awareness was low among middle-grade students of the age group (12-15) in comparison to secondary-level students of the age group (15-18). The study emphasises incorporating structured cyber safety education in school curricula and building teacher capacity through continuous professional development, leading to the development of responsible, informed, and digitally resilient citizens.